Intravaginal Administration of Interleukin 12 during Genital Gonococcal Infection in Mice Induces Immunity to Heterologous Strains of Neisseria gonorrhoeae - Yingru Liu (American Society for Microbiology, 2018)
ABSTRACT It has previously been shown that genital tract infection with Neisseria gonorrhoeae in mice does not induce a state of protective immunity against reinfection but instead suppresses the development of adaptive immune responses against N. gonorrhoeae dependent on transforming growth factor beta (TGF-β) and interleukin 10 (IL-10). Intravaginal administration during gonococcal infection of IL-12 encapsulated in biodegradable microspheres (IL-12/ms) reverses the immunosuppression and promotes the production of gamma interferon (IFN-γ) and of specific antibodies in serum and genital secretions and accelerates clearance of the infection. In this study, microspheres were shown to remain largely within the genital tract lumen and to release IL-12 over the course of 4 days. Antigonococcal IgA and IgG antibodies induced by IL-12/ms treatment reacted with antigenically different strains of N. gonorrhoeae and led to resistance to reinfection with heterologous and homologous strains. Immune resistance to reinfection persisted for at least 6 months after clearance of the primary infection. Experiments performed with immunodeficient strains of mice lacking either IFN-γ or B cells demonstrated that both IFN-γ and B cells were necessary for the IL-12-induced generation of immune responses to N. gonorrhoeae and the resulting accelerated clearance of the infection. It is therefore concluded that intravaginally administered IL-12/ms achieves its effect by the sustained release of IL-12 that promotes Th1-driven adaptive immune responses, including the production of specific antigonococcal antibodies that cross-react with multiple strains of N. gonorrhoeae. IL-12-enhanced immunity to N. gonorrhoeae can be recalled against reinfection after prolonged intervals and is dependent upon both IFN-γ and antibody production by B cells. IMPORTANCE Genital infection with Neisseria gonorrhoeae (gonorrhea) is a significant cause of reproductive tract morbidity in women, leading to pelvic inflammatory disease, tubal factor infertility, and increased risk for ectopic pregnancy. WHO estimates that 78 million new infections occur annually worldwide. In the United States, >350,000 cases are reported annually, but the true incidence is probably >800,000 cases/year. Increasing resistance to currently available antibiotics raises concern that gonorrhea might become untreatable. Infection does not induce a state of immune protection against reinfection. Previous studies have shown that N. gonorrhoeae suppresses the development of adaptive immune responses by mechanisms dependent on the regulatory cytokines TGF-β and IL-10. This study shows that intravaginal treatment of gonococcal infection in female mice with microencapsulated IL-12 induces persisting anamnestic immunity against reinfection with N. gonorrhoeae, even of antigenically diverse strains, dependent on T-cell production of IFN-γ and B-cell production of antibodies.